2003
DOI: 10.1177/0148607103027004241
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supplemental enteral glutamine on plasma levels, gut function, and outcome in severe burns: a randomized, double‐blind, controlled clinical trial

Abstract: Enteral gln supplementation using a commercially available dipeptide supported plasma gln levels, improved gut permeability, and initially decreased plasma endotoxin levels in severely thermally injured patients. These alterations were associated with a reduction in the length of hospitalization and lower costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(124 citation statements)
references
References 13 publications
2
108
0
14
Order By: Relevance
“…Numerous animal studies and a few studies in catabolic patients have shown that enteral Gln improves gut barrier function as measured by bacterial translocation in animals [35] and gut permeability to sugar markers in humans [13]. In the current study, the lactulose/mannitol urinary excretion ratio was approximately twice as high as in a group of 10 healthy controls in our laboratory (not shown), but was unaffected by Gln dipeptide administration by either route.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Numerous animal studies and a few studies in catabolic patients have shown that enteral Gln improves gut barrier function as measured by bacterial translocation in animals [35] and gut permeability to sugar markers in humans [13]. In the current study, the lactulose/mannitol urinary excretion ratio was approximately twice as high as in a group of 10 healthy controls in our laboratory (not shown), but was unaffected by Gln dipeptide administration by either route.…”
Section: Discussionsupporting
confidence: 48%
“…During critical illness, Gln may become conditionally indispensable as evidenced by the fall in plasma and tissue concentration apparently as a result of Gln utilization exceeding endogenous production [5][6][7]. Previous studies suggest that improved plasma Gln concentrations may be beneficial for patients with critical illnesses to improve GSH biosynthesis in tissues [8], nitrogen balance [9], immune function [10][11][12], intestinal permeability [13] and the incidence of hospital-acquired infection [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wyniki tych badań i metaanaliz zostały przedstawione w podrozdziale dotyczącym intensywnej terapii [17][18][19]. Badania, w których stosowano dojelitowe leczenie żywieniowe wzbogacone tylko w glutaminę, przeprowadzano także w heterogennych grupach pacjentów OIT (wyniki przedstawiono w rozdziale dotyczącym intensywnej terapii [20][21][22]). Na ich podstawie nie można jednoznacznie podać zaleceń dotyczących stosowania dojelitowo glutaminy u chorych poddawanych zabiegom chirurgicznym.…”
Section: Zalecenia Espen Dla Chorych Poddawanych Zabiegom Chirurgicznymunclassified
“…Podobne badanie przeprowadzili także Zhou i wsp. [20], którzy 40 chorym po rozległych oparzeniach (50-80% powierzchni ciała) podawali dojelitowo przez 12 dni dietę standardową wzbogaconą w dipeptyd Ala--Gln (0,35 g/kg/dobę) lub niewzbogaconą. W grupie otrzymującej dipeptyd Ala --Gln poziom LPS był istotnie niższy (od 3. doby), a czas hospitalizacji istotnie krótszy niż w grupie żywionej standardowo.…”
Section: Intensywna Terapiaunclassified